PERAN LITERASI DIGITAL, ADAPTABILITAS DAN SELF EFFICACY DALAM MEMENGARUHI KESIAPAN KERJA GEN Z DI ERA TRANSFORMASI TEKNOLOGI - Karimah, Isnah; Muhammad Nuskan Abdi; Mufid, Muhammad (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2025)
This study aims to analyze the influence of digital literacy, adaptability, and self-efficacy on Generation Z's work readiness, while also comparing the effects between senior high school students and college/diploma students. A quantitative approach was applied using an associative-comparative method. The population included high school and university students in the Pekalongan region, with a total of 200 respondents selected through convenience sampling. Data were collected via a questionnaire that had undergone validity and reliability testing. Multiple linear regression analysis was used to determine the impact of each independent variable on work readiness, while an independent samples t-test was conducted to examine differences between the two groups. The findings indicate that digital literacy and self-efficacy significantly and positively affect work readiness, whereas adaptability does not show a significant impact. Moreover, the comparison test revealed that university students demonstrate higher levels of work readiness, digital literacy, and self-efficacy than high school students. However, no significant difference was found in adaptability. These results highlight the importance of enhancing digital literacy and self-efficacy from secondary education levels to improve Generation Z's readiness for employment.